Peranan Organisasi Ikatan Harmonis Santri Ainul Yaqin (Ihsan) Meningkatkan Kedisiplinan Santri di Pondok Pesantren Modern Ainul Yaqin Sawah Liek Kenagarian Batagak Kecamatan Sungai Pua Kabupaten Agam - Prategi, Diana; F, Fauzan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to scientifically describe the role of the Ainul Yaqin Santri Harmony Association Organization (IHSAN) in improving the discipline of santri at the modern Islamic boarding school Ainul Yaqin Sawah Liek Kenagarian Batagak. The author uses a descriptive research method with a qualitative approach, because the author describes how the role of the Ainul Yaqin Santri Santri Harmonious Association Organization (IHSAN) improves the discipline of santri at the Ainul Yaqin Sawah Liek modern Islamic boarding school. In collecting data, the author made observations first, conducted interviews and continued with documentation. In collecting information, the author used two informants, namely the key informant, the IHSAN administrator and the supporting informants, namely the IHSAN supervisor, the vice chairman of the Islamic boarding school and the santri at the Islamic boarding school. The data examination technique is using triangulation. The role of the IHSAN/OSIS organization is very important in improving student discipline, namely: 1). IHSAN acts as a forum for students by using a deliberation forum to discuss. existing disciplinary regulations. 2). IHSAN acts as a motivator and driver, namely by providing motivation and appreciation to students who are diligent and have high disciplinary values. 3). IHSAN acts as a student mentor, namely providing guidance in the form of religious activities such as scheduling student worship. and congregational prayers. 4). IHSAN acts as a preventive measure, namely dealing with students who violate it with preventive measures in the form of punishment.